Rights to social determinants of flourishing? A paradigm for disability and public health research and policy - Maria Berghs; Karl Atkin; Chris Hatton; Carol Thomas (BMC, 2019)
Abstract Background The term evidence based medicine was introduced in the early 1990s in clinical medicine to educate clinicians about how to assess the 'credibility' of research to ensure best treatments for their patients. The evidence based medicine paradigm has become more diffuse in times of austerity and randomised controlled designs are being used to address complex issues in public health and disability research. This research is not addressing inequalities in terms of disability nor how people can live well with disabilities. Main text We argue that there are four ways that public health research needs to change if it wants to address inequalities linked to disability: 1) rethinking theoretical connections between public health and disability; 2) building ethics and equity into interventions through a human rights approach; 3) ensuring ethical inclusion through intersectionality; and 4) evaluating policy and other social impacts to ensure they capture diversity. We argue that these are key issues to building a social determinants of flourishing. Conclusions We need to understand how disability might have an accumulative impact across the life course, as well as how to ensure equity for people living with disabilities. This means conceptualising a social determinants of flourishing where we evaluate how exactly randomised controlled trials and public health interventions, not only lead to greater equality but also ensure rights to health and wellbeing.